Role of bacterial biofilms and their EPS on settlement of barnacle (Amphibalanus reticulatus) larvae. (May 2020) - Rajitha, K.; Nancharaiah, Y.V.; Venugopalan, V.P.
Abstract: Settlement of pelagic cypris larvae is crucial for barnacle biofouling which causes severe operational problems and economic penalties in maritime activities and seawater cooled power plants. Marine biofilms formed on submerged surfaces play a key role in settlement of larvae of barnacles and a promising source for environmentally benign antifouling strategies. To determine inhibitory action of biofilms, bacterial strains were isolated from natural biofilms, screened for their biofilm formation potential and interference in settlement of cyrpis larvae of Amphibalanus reticulatus. Monoculture biofilms of three bacterial strains i.e. Alteromonas sp. 1, Alteromonas sp. 2 and Bacillus cereus inhibited cypris settlement by 67%–93% and 67%–78% in choice and no choice experiments, respectively. Biofilms of two bacterial strains ( B. pumilus and Halomonas aquamarina ) had no significant effect and one strain ( Brevibacterium casei ) showed marginal induction in cypris settlement. In case of inhibitory biofilms, the inhibitory action on cypris could be ascertained to the loosely bound extracellular polymeric substances (LB EPS). The effects of LB EPS included settlement inhibition, larval mortality, altered larval behaviour and interrupted moulting. Crude fractionation and testing of individual LB EPS fractions showed that the inhibitory activity was associated with the carbohydrate components. This study shows the importance of further studies on probing marine biofilm-larval interactions, identification and characterization of inhibitory compounds for developing newer environmentally benign antifouling strategies. Graphical abstract: Image 1 Highlights: Monospecies bacterial biofilms showed inhibitory effect or no effect on barnacle larvae. Alteromonas and Bacillus biofilms prevented settlement of barnacle larvae. Loosely bound extracellular polymeric substances (LB EPS) of biofilms inhibited barnacle larval settlement. Extracted LB EPS induced mortality and precocious metamorphosis in barnacle larvae. The inhibitory activity of LB EPS was assigned to carbohydrate components.